2012
DOI: 10.1073/pnas.1119112109
|View full text |Cite
|
Sign up to set email alerts
|

Jumonji domain-containing protein 3 regulates histone 3 lysine 27 methylation during bovine preimplantation development

Abstract: Understanding the mechanisms of epigenetic remodeling that follow fertilization is a fundamental step toward understanding the bases of early embryonic development and pluripotency. Extensive and dynamic chromatin remodeling is observed after fertilization, including DNA methylation and histone modifications. These changes underlie the transition from gametic to embryonic chromatin and are thought to facilitate embryonic genome activation. In particular, trimethylation of histone 3 lysine 27 (H3K27me3) is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 49 publications
(69 reference statements)
5
61
2
1
Order By: Relevance
“…The Jmjd3 −/− mice that we have generated out of the ESCs, used in the present study, showed embryonic lethality before E6.5, suggesting a crucial role of Jmjd3 in early embryonic development Figure VII). This is consistent with the requirement of Jmjd3 for blastocyst development, 27 but is in contrast to other studies which showed that Jmjd3-deficient mice are perinatal lethal. 12,28 The discrepancy between the phenotypes of Jmjd3…”
Section: Discussionsupporting
(Expert classified)
“…The Jmjd3 −/− mice that we have generated out of the ESCs, used in the present study, showed embryonic lethality before E6.5, suggesting a crucial role of Jmjd3 in early embryonic development Figure VII). This is consistent with the requirement of Jmjd3 for blastocyst development, 27 but is in contrast to other studies which showed that Jmjd3-deficient mice are perinatal lethal. 12,28 The discrepancy between the phenotypes of Jmjd3…”
Section: Discussionsupporting
(Expert classified)
“…Methylation at the H3K27 residue is mediated by the PRC2 complex (31), and demethylation is mediated by histone demethylases KDM6A (also known as UTX) and KDM6B (also known as JMJD3) (32). A recent study showed that KDM6B is involved in regulating global H3K27Me3 levels in bovine preimplantation embryos (33). In addition, studies in mESCs showed that JARID2 (also known as Jumonji) orchestrates PRC2 function and fine-tunes deposition of the H3K27Me3 mark at chromatin domains (34)(35)(36)).…”
Section: Resultsmentioning
confidence: 99%
“…H3K27me3 has a great effect on embryonic development. For example, the embryonic development was reduced after inhibition of H3K27me3 removal in bovine (Canovas et al 2012). Similarly, iPS reprogramming process was also accompanied by genome wide H3K27me3 changes, and the aberrant dynamics of H3K27me3 would impair iPS cells induction (Mikkelsen et al 2008, Hawkins et al 2010, Mansour et al 2012.…”
Section: Introductionmentioning
confidence: 99%